Diseño de una guía para la implementación de un sistema integrado con los referentes OHSAS 18001:2007, ISO 14001:2004, RUC: 2014 para las estaciones de servicio de inversiones Coomotor s.a. (2015)
The present work is based on a diagnosis made in each service station of Inversiones Coomotor S.A. located in Neiva-Huila in which the services of fuel supply, oil change, alignment and balancing are provided. Specific problems were identified regarding types of work incidents; limited training for staff, workers, contractors, suppliers and customers; inadequate treatment to the consumables used in service stations such as waste, used oil, filters, used tires. Therefore, a guide was designed for the implementation of an Integrated System with the referents OHSAS 18001: 2007, ISO 14001: 2004, RUC: 2014 for the Service Stations of Inversiones Coomotor S.A. (EDS COOMOTOR, EDS COOMOTOR SOUTH, EDS COOMOTOR NORTH) located in the city of Neiva-Huila. In this way, reduce the work incidents and reduce the negative impacts to the environment, optimizing each of the processes, achieving in an indirect way the reduction of costs in the processes developed in each of the service stations; increasing sustainability and promoting the growth of the company, under a Colombian legal framework of mandatory compliance.